Analisis Hasil Belajar Matermatika Dalam Pembelajaran Daring Menggunakan Aplikasi Whatsapp Group - Putwi Veranika; Su'ad Su'ad; Ratri Rahayu (WASIS : Jurnal Ilmiah Pendidikan, 2022)
This study aims to describe the results of learning mathematics during the online learning process and the obstacles in using the whatsapp group application in fourth grade elementary school students.This research is a qualitative research with the type of narrative research which was carried out in SD 2 Mlati Lor, Kota District, Kudus Regency. The subjects in this study were 6 students, 3 boys and 3 girls. Data collection techniques used observation, interviews and documentation. Data analysis used is data reduction, data presentation, and drawing conclusions. The results of the research obtained are that online learning using the Whatsapp Group application at SD 2 Mlati Lor runs well according to the applicable educational standards.The results showed that all educational units were on average in online learning using the Whatsapp Group Application. The results of learning mathematics at SD 2 Mlati Lor during online learning are good, as indicated by the complete score of all students. There are obstacles in the use of Whatsapp Group as a learning medium at SD 2 Mlati Lor, namely signal interference, lack of motivation, inadequate facilities, difficulty in understanding the material, full mobile memory and too many tasks.